2019
DOI: 10.1142/s1793524519500475
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a delayed diffusive model with Beddington–DeAngelis functional response

Abstract: In this paper, a delayed diffusive phytoplankton-zooplankton model with Beddington–DeAngelis functional response and toxins is investigated. Existence of equilibria of the system are solved. The global asymptotic stability of the zooplankton-free equilibrium is obtained. The local stability of the coexistent equilibrium and existence of Hopf bifurcation are discussed. In addition, the properties of the Hopf bifurcation are studied based on the center manifold and normal form theory for partial differential equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…On the other hand, there should be a period for a drug user in treatment before he relapses into the physiological addicts due to the effect of treatment and his self-control. With an eye to such considerations and motivated by the work of some other dynamical systems with time delay [26][27][28][29][30], we investigate a more realistic synthetic drugs transmission model as follows:…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there should be a period for a drug user in treatment before he relapses into the physiological addicts due to the effect of treatment and his self-control. With an eye to such considerations and motivated by the work of some other dynamical systems with time delay [26][27][28][29][30], we investigate a more realistic synthetic drugs transmission model as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Of course, it also satisfies the need for humans to benefit from natural resources. The prey-predator systems with harvesting have been widely studied by a large number of scholars [13,[18][19][20][21][22][23]. Meng et al [19] studied a predator-prey system with harvesting prey and disease in prey species and found that the optimal harvesting effort is closely related to the incubation period of the infectious disease, and the maximum value of the optimal harvesting decreases with the increase of the time delay.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al demonstrated that time delay can affect stability of a dynamical system and cause nonlinear phenomena such as Hopf bifurcation and periodic solutions [25,26]. For some other works about dynamical systems, one can refer to [27][28][29][30]. Therefore, it is very crucial to examine the effect of the time delay τ on system (1).…”
Section: Introductionmentioning
confidence: 99%